Comparison of automated quantification and semiquantitative visual analysis findings of IQ SPECT MPI with conventional coronary angiography in patients with stable angina - Cem Doğan; Ferahnaz Çınaral; Ali Karagöz; Zübeyde Bayram; Selami Çağatay Önal; Özkan Candan; Rezzan Deniz Acar; Murat Çap; Emrah Erdoğan; Aykun Hakgör; Özgür Yaşar Akbal; Abdulkadir Uslu; et al. (KARE Publishing, 2019)
Objective: The aim of this study was to assess the validity of automated quantitative and semiquantitative visual analysis of total perfusion deficit (TPD) using the IQ SPECT gamma camera system compared to conventional coronary angiographically detected significant coronary artery disease (CAD). Methods: The study included patients with suspected CAD who underwent myocardial perfusion single photon emission computed tomography and conventional coronary angiography. The summed stress score (SSS), summed rest score (SRS), and summed difference score (SDS) (semiquantitative visual analysis results) were assessed using a 5-point scale in a standard 17-segment model, and TPD (stress, rest, and ischemic TPD) was quantified using automated software. Results: In all, 84 patients (Group 1, those who underwent revascularization) had significant coronary artery lesions, and 81 (Group 2) had non-significant lesions. The median interquartile range values were: stress-TPD (sTPD): 16 (3.5- 33.5) vs 9.2 (2-17.9), rest-TPD: 9.4 (2.2-18.8) vs 4 (1-11), and 6.9 (1.9-14.1) vs 3.4 (1-6.1) for ischemic-TPD (iTPD) in Group 1 and Group 2, respectively. To detect ischemia, the optimal cut-off points were 9.5 (sensitivity: 75%, specificity; 60%) for sTPD, and 4.5 (sensitivity: 56%, specificity: 73%) for iTPD. There were significant correlations between quantitative and semi-quantitative methods in detection of significant coronary artery disease (sTPD-SSS: r=0.954, sTPD-SDS: r=0.746, iTPD-SSS: r=0.654, iTPD-SDS: r=0.759; p<0.05 for all). Conclusion: The quantitative analysis and summed stress scores produced by the IQ SPECT system appear to be a useful and valid method to detect significant CAD.